SOCIEDADE, CRISE POLÍTICA E DISCURSO HISTÓRICO-LITERÁRIO NA ROMA ANTIGA - Cardoso, Ciro Flamarion (PHOÎNIX, 2020)
This paper focuses on the difference i t intellectual attitudes regarding the tribunate of Tiberius Gracchus and the crisis of 133 BC one perceives when comparing the opinions of authors who wrote at the end of the Roman Republic, such as Sallust or Cicero, to those of authors writing under the Principate, such as Plutarch and Appian. In the end, in spite of some differences, the basic political and social stance is in fact quite similar. In discussing this issue, the text is mainly attentive to political situations and social contexts. Questions pertaining to what could be considered constitutionally legal or illegal during the last century of the Roman Republic are also addressed.